Analisis Perbandingan Penggunaan Celebrity Endorser Dan Typical-Person Endorser Iklan Televisi Dan Pengaruhnya Terhadap Brand Image Produk Shampo Clear - Yunianto, Tri; Hidayah, Arini (Media Ekonomi, 2017)
This study aims to determine the effects difference and typical celebrity endorser endorser in the ad-person sampho Clear and determine the effect of typical celebrity endorser-person and endorser of the brand image of products sampho Clear. This study is a survey with a population of m students Muhammadiyah University of Navan user and Clear shampoo sample of 97 respondents. Data analysis using independent sample t test analysis, multiple linear regression analysis with t test and F test. The results showed that there are differences in usage and the typical endorser Celebrity endorsers in advertising-person sampho Clear. Based on t test results obtained for 2.976 t count bigger than t table 1.653. celebrity endorser significant effect on brand image Clear shampoo brand. Value of 6.041 t count bigger than t table 1.987. typical-person endorser significant effect on brand image Clear shampoo brand. Value of 3.417 t count bigger than t table 1.987. Keywords: Celebrity endorsers, Typical-Person endorser, Brand Image